Variáveis preditoras da doença renal crônica e suas comorbidades em gatos (Felis catus) - Tathiana Mourao dos Anjos (2018)
A chronic kidney disease is a more common feline kidney disease, especially in middle-aged cats and the elderly. Comorbidities such as metabolic diseases, infectious diseases and neoplasms are quite frequent in cats. 168 healthy cats and 168 chronic kidney patients were selected, with and without associated comorbidities. The animals were reached in clinical, laboratory and imaging. The main objective of the present study was to identify and correlate as predictive variables of chronic kidney disease and its main comorbidities. Data were analyzed through univariate and multivariate statistical analyzes. It was possible to identify predictive variables of feline chronic kidney disease and of different comorbidities, as well as to demonstrate the strong influence of its occurrence on the prognosis of feline chronic kidney patients. Clinical-laboratory decision trees were created to aid in the diagnosis and conduct of the chronic renal patient feline patient with some type of comorbidity, associated or not with chronic kidney disease. Thevariables that most predict death outcome in cats with chronic kidney disease are: urea, creatinin, phosphorus, amylase, hemoglobin, globular volume, total leukocytes, segmented neutrophils, globulin, blood pressure, urinary density, total protein and UPC. And the clinical signs are: prostration, weight loss, uremic encephalopathy, pain, uremic stomatitis, cervical ventroflexion/plantar posture, nausea, vomiting, mucosal Paleness, polyuria / polydipsia, and dehydration.